The application of video tutorials in student learning at a peruvian university (Revista Electrónica Calidad en la Educación Superior, 2021)
The research was carried out with the aim of demonstrating that the application of the video tutorial increases the learning of the subject of Public Management in the students of the Professional School of Administration. The work is of an applicative type, has the quasi-experimental design, with two balanced groups, one experimental and one control. The population was made up of students of the specialty of Administration. The sample was induced, being the students of the ninth cycle, conformed by 46 students, to which three tests were applied: conceptual, procedural and attitudinal. The results showed that there is a significant improvement in student learning. Finally, it was demonstrated that the application of video tutorials improves the learning of the subject of Public Management.
Keywords: Public management, Audiovisual, Communication, Information technology, Education